Enseñanza biblioteconómica en el marco de la universidad «Transilvania» de Brasov-Rumanía - Popa, Silvia; Pirnuta, Oana-Andreea (Revista General de Información y Documentación, 2003)
The aim of this article is to give a brief introduction to the specialization Library Science- Museum Studies at the University College within the framework of the «Transilvania» University of Brasov, Rumania. The curriculum is analyzed focusing on the Laboratory of Library Science set up by means of the COLLIMUS (College of Library Science and Museum Studies) Project. The role of the Center for Bibliographical Research in bringing improvements to the teaching process and enriching national and international cooperation is highlighted.